STUDI BIAYA KECELAKAAN DI PERLINTASAN SEBIDANG BERPALANG PINTU DAN TANPA PALANG PINTU DI JAWA TIMUR - Leliana, Arinda; Soimun, Ahmad; Puspitasari, Armyta; Apriliani, Nurul Fitria (LPPM, 2024)
Losses due to accidents, especially at level railroad crossings, cause losses that are in line with the extent of accidents. The value of losses arising from accidents was studied to increase public awareness about the number of losses, both material and non-material losses. Each element of accident costs is assessed by gross power according to Pd.T-02-2005-B. The characteristics of traffic accidents are identified based on several factors including gender, transportation mode, and factors that cause accidents. Afterward, calculate the value of each element of the accident cost and the total accident cost. Victim’s estimated unit cost and the traffic accidents unit cost at railroad level crossings with barriers and without showing the result that the highest average per year is IDR 1.490.758.906 per accident. The amount of average traffic accident cost per year at railroad level crossing on intercity roads for the highest incident is IDR 1.241.181.688 per accident. The average traffic accident per year at railroad level crossing on city roads for the highest incident is IDR 863.664.801 per accident. The accident factors are shoving through a railroad level crossing, carelessness when crossing the railroad level crossing, disregarding signs when a train is about to pass, and being vigilant to warning signs when crossing a level crossing.